Laser-induced dielectric anisotropy of a hybrid liquid crystal composite made up of methyl red and fullerene C60 - San, SE; Köysal, O; Okutan, M (Elsevier, 2005)
Electro-optical properties of a hybrid liquid crystal composite are investigated in the presence of laser-induced effects. in the scope of this work, various measurements were performed to analyze the effect of laser pumping on molecular reorientation. Electro-optical parameters are investigated under dark and laser-induced conditions for fullerene-doped and undoped samples. Experimental results show a dependence on laser pumping of the switching voltage for reorientation. Dielectric anisotropy is also studied for the mentioned conditions and its dependency is quantatively estimated by capacitive measurements. (c) 2005 Elsevier B.V. All rights reserved.
3rd International Conference on Broadband Dielectric Spectroscopy and its Applications -- AUG 23-26, 2004 -- Delft, NETHERLANDS
Keywords: Azo-Dye; Host